Habilidades interpersonales y su incidencia en la inclusión educativa - Fernández Robalino, Paola Dennis (2024)
The objective of this research was to analyze the influence that the development of interpersonal skills has had in children with cases of inclusion, since it facilitates effective communication, cooperation between individuals and affinity, instead helping to establish a positive and inclusive learning scenario. In the methodological design, a mixed approach and a descriptive scope were used, among the instruments that were used were interviews with teachers of 4 children between the ages of 9 and 11 years, who present certain problems of being able to relate in the classroom with their classmates and teachers; who were referred to the DECE in order to learn about their cases and where the teachers had to carry out methodological strategies according to their inclusion in the classroom, for which in order to develop and enhance interpersonal and social skills. In what after carrying out an observation test and an interpersonal skills test, their results tell us that they have a LOW LEVEL in the social skills test, therefore it is asked that teachers apply in a deeper way all their teaching and learning methodologies within the classroom, using tools and resources, whether playful or digital, in order to go out and cover the problems of the 4 children.